Produção de conteúdo gamer - Cardozo, Missila Loures (2020)
This research focuses on the production of gamer content, with an emphasis on video production. To this end, the issues of transmedia adaptation, social networks and the universe of fans, the game market, media franchises and the production of game-based content, such as videos for YouTube, will be addressed. The goal is to understand the nature of adaptations, the universe of fandom and the relationship with producers. In general, we will discuss the aspects and characteristics of games and adaptations and theories. The main findings of the research are that the production of content takes place, mostly, independently of the developers and that the consumption of this content is increasing, as a form of entertainment